Case report: A rare case of pyruvate kinase deficiency and Crigler-Najjar syndrome type II with a novel pathogenic variant of PKLR and UGT1A1 mutation - Wu, Huan; Wu, Long; Zhang, Quan; Zhang, Bao-fang (Frontiers in Genetics, 2023)
Pyruvate Kinase Deficiency (PKD) and Crigler-Najjar syndrome are rare autosomal recessive liver disease. PKD is caused by homozygous or compound heterozygous mutations in the PKLR gene, leading to non-spherocytic hereditary hemolytic anemia. On the other hand, Crigler-Najjar syndrome(CNS-II) is characterized by the loss or reduced activity of UDP-glucuronosyltransferase, resulting in elevated levels of unconjugated bilirubin, which is the primary cause of disease manifestation. To date, there have been no reported cases of patients with both conditions. In this case report, we present a unique clinical course of a in a 15-year-old Chinese patient with both PKD and CNS-II. The patient was admitted for evaluation of hyperbilirubinemia and exhibited yellowish skin color, icteric sclera, and splenomegaly upon physical examination. Extensive laboratory examinations ruled out viral, hemolytic, autoimmune, and inborn or acquired metabolic etiologies of liver injury. Histopathological findings indicated benign recurrent intrahepatic cholestasis (BRIC) and hemosiderosis. Surprisingly, targeted next-generation sequencing (NGS) of the patient's blood did not reveal any mutation sites associated with BRIC. Instead, it identified a novel homozygous pathogenic variant of the PKLR gene [c.1276C>T (p.Arg426Trp)] and a rare heterozygous variant of UGT1A1 gene [c.-55_-54insAT, c.1091C>T (p.Pro364Leu)]. These findings strongly suggested a diagnosis of PKD and CNS-II in the patient. Treatment with 500 mg/day of ursodeoxycholic acid proved to be effective, rapidly reducing the patient's total bilirubin levels and shortening the symptomatic period. This case highlights the importance of genetic diagnosis in accurately identifying the underlying cause of hyperbilirubinemia, especially in patients with rare hereditary diseases. Furthermore, NGS can provide valuable insights into the genotype-phenotype correlation of PKD and CNS-II.